Karst aquifer hazard assessment and mapping on the Classical Karst - Nataša Ravbar (Acta Geographica Slovenica, 2006)
The article presents potential and actual sources of groundwater contamination on the Kras plateau, which is the recharge area of the Klariči karst water source that provides drinking water for the Kras plateau and Koprsko primorje. The water source is insufficiently protected due to inadequate water protection policy and the control over the implementation of the provisions has often been ineffective. Untreated wastewaters, illegal waste-disposal dumps and traffic endanger the water source. The hazards are shown on a simplified map that could be, in a suitable scale, a valuable practical tool for further water source protection and in land-use planning.